The crystal structures of chloramphenicol phosphotransferase reveal a novel inactivation mechanism - Izard, Tina (Oxford University Press, 2000)
Chloramphenicol (Cm), produced by the soil bacterium Streptomyces venezuelae, is an inhibitor of bacterial ribosomal peptidyltransferase activity. The Cm-producing streptomycete modifies the primary (C-3) hydroxyl of the antibiotic by a novel Cm-inactivating enzyme, chloramphenicol 3-O-phosphotransferase (CPT). Here we describe the crystal structures of CPT in the absence and presence of bound substrates. The enzyme is dimeric in a sulfate-free solution and tetramerization is induced by ammonium sulfate, the crystallization precipitant. The tetrameric quaternary structure exhibits crystallographic 222 symmetry and has ATP binding pockets located at a crystallographic 2-fold axis. Steric hindrance allows only one ATP to bind per dimer within the tetramer. In addition to active site binding by Cm, an electron-dense feature resembling the enzyme’s product is found at the other subunit interface. The structures of CPT suggest that an aspartate acts as a general base to accept a proton from the 3-hydroxyl of Cm, concurrent with nucleophilic attack of the resulting oxyanion on the γ-phosphate of ATP. Comparison between liganded and substrate-free CPT structures highlights side chain movements of the active site’s Arg136 guanidinium group of >9 Å upon substrate binding.